Optical illusions in fashion design. (Journal of the College of Basic Education, 2022)
Like other arts, fashion design has been affected by various artistic trends. The art of fashion design has evolved and has been devoted to scientific and technical studies and specialized experts with good standards for the concept of design, in line with the technical foundations followed in modern schools.The school of visual deception is considered one of the important technical schools that play a prominent role in designing costumes that address the defects of the human body, which are due to excess or lack of weight, as well as some other hidden defects, by giving them the impression of being underweight, or perhaps an increase in height, or reducing The severity of the fullness of some parts, or the thinness of other parts, due to the characteristics and characteristics of this school.The researcher directed in his theoretical framework to study the technical foundations of the art of visual deception, as well as